Radiotherapy: An Update - Vikrant Kasat; Sunil Sahuji; Manjiri Joshi (Wolters Kluwer Medknow Publications, 2010)
Radiotherapy is the art of using ionizing radiation to destroy malignant cells while minimizing damage to normal tissue. Radiotherapy has become a standard treatment option for a wide range of malignancies. Several new imaging techniques, both anatomical and functional are currently being evaluated as well as practiced for treatment planning of cancer. These recent developments have allowed radiation oncologists to escalate the dose of radiation delivered to tumors while minimizing the dose delivered to surrounding normal tissue. In this update, we attempt to pen down important aspects of radiotherapy.